Study on the safety detection of pesticide residues in agricultural products by means of chromatography - Wang, Yujie (EPJ techniques and instrumentation, 2025)
This paper mainly studied the safety detection of pesticide residues of agricultural products. The agricultural products studied were capsicums from Haidong City, Qinghai Province, China. Ten kinds of organophosphate pesticides (OPPs) were detected by the quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction combined with gas chromatography-tandem mass spectrometry (GC-MS/MS). The results showed that the method had the best detection performance when using 1% glacial acetic acid-acetonitrile solvent as extraction agent and 0.6gMgSO4+0.1gPSA+0.1GGCB as purification agent. The average recovery rate of ten OPPs was between 75.94% and 118.78%, and the relative standard deviation (RSD) was between 1.01% and 3.25%. In the actual detection of 216 capsicum samples, only methidathion was detected twice, the detection range was 0.0018-0.0026 mg/kg, and the maximum residue limit was 0.2 mg/kg; all ten kinds of OPPs were within the standard limits. The results show that this method can detect ten kinds of OPPs in agricultural products and can be applied in practice.